1987
DOI: 10.1002/ar.1092170203
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the density of spermatogonia in the seminiferous epithelium of the Chinese hamster: I. Undifferentiated spermatogonia

Abstract: The topographical arrangement of the clones of A single, A paired, and A aligned (As, Apr, and Aal) spermatogonia on the basement membrane of seminiferous tubules of the Chinese hamster was studied. It was found that at least some of these clones are not distributed at random as clones of similar cell number were often seen in clusters. Areas were found with few or many As spermatogonia. Also, clusters of Apr spermatogonia were found, indicating that in such an area many As spermatogonia more or less synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 9 publications
0
38
0
1
Order By: Relevance
“…In line with this, the numbers of clones of GFRA1C Aal4 were markedly reduced and GFRA1C Aal8 were even absent in stages VII-VIII. Since under physiological conditions apoptosis takes place in differentiating spermatogonia but not in undifferentiated spermatogonia (de Rooij & Janssen 1987, de Rooij & Lok 1987 we interpret this as a consequence of the progression of GFRA1C Aal clones into the next differentiation compartment. In addition, we found that Kit mRNA levels were significantly upregulated by GDNF during stages II-VIII.…”
Section: Discussionmentioning
confidence: 93%
“…In line with this, the numbers of clones of GFRA1C Aal4 were markedly reduced and GFRA1C Aal8 were even absent in stages VII-VIII. Since under physiological conditions apoptosis takes place in differentiating spermatogonia but not in undifferentiated spermatogonia (de Rooij & Janssen 1987, de Rooij & Lok 1987 we interpret this as a consequence of the progression of GFRA1C Aal clones into the next differentiation compartment. In addition, we found that Kit mRNA levels were significantly upregulated by GDNF during stages II-VIII.…”
Section: Discussionmentioning
confidence: 93%
“…This either means increased proliferative activity of the undifferentiated spermatogonia in p53 knock out mice, suggesting a role of p53 in the regulation of the normal cell cycle of these cells, or a decreased apoptosis of undifferentiated spermatogonia in p53 knock out mice. Apoptosis of differentiating type A spermatogonia in the normal testis has been described extensively by a number of groups (Rodriguez et al, 1997;Furuchi et al, 1996;Allan et al, 1992) and could be useful in removal of aberrant cells and/or regulation of cell density (De Rooij and Lok, 1987;De Rooij and Janssen, 1987). So far, no degeneration/apoptosis of undifferentiated spermatogonia in the normal testis has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, different areas in relevant epithelial stages contain widely variable numbers of A1 spermatogonia. Nevertheless, the density distribution of In and B spermatogonia and preleptotene spermatocytes appeared to be rather even (de Rooij and Janssen, 1987;de Rooij and Lok, 1987). The evening-out of the cell density occurs among A1-A4 spermatogonia.…”
Section: Germ Cell Density Regulation In the Spermatogonial Compartmentmentioning
confidence: 91%